The Urgency of Integrating Restorative Justice Provisions into the Draft Criminal Procedure Code (RUU KUHAP) as a Form of Justice Reform: Urgensi Integrasi Pengaturan Restorative Justice dalam RUU KUHAP sebagai Bentuk Reformasi Keadilan - Muttaqi, Nabila Ihza Nur (Universitas Islam Indonesia, 2025)
Criminal law is closely associated with the stigma of imprisonment, which often creates justice issues for the parties involved due to an unequal standing. This situation has led to the introduction of concepts such as Restorative Justice, which aim to resolve criminal cases by involving all parties—including offenders, victims, and the community. However, various regulations governing Restorative Justice exist across different institutions, including the Police, the Prosecutor's Office, and the Supreme Court. This inconsistency adversely impacts implementation, resulting in difficulties aligning one regulation with another within the criminal justice system. This paper aims to examine the regulatory challenges surrounding Restorative Justice at the Indonesian regulatory level and the importance of integrating Restorative Justice regulations into the Criminal Procedure Bill. Conducted as normative legal research, this study employs both a statutory approach and a conceptual approach. The legal materials utilized include primary, secondary, and tertiary sources, which are organized descriptively for qualitative analysis. The research findings indicate that significant issues arise from differing interpretations and inconsistencies within the existing regulations of the Indonesian criminal justice system. Therefore, there is a pressing need to consolidate the various regulations into a coherent framework for Restorative Justice, allowing for optimal implementation of its principles. It is hoped that legislative institutions, as key stakeholders and decision-makers in legal policy, will consider adopting the Restorative Justice concept within the Criminal Procedure Code Bill.